Mechanical properties of the hyomandibula in four shark species. Issue 1 (5th November 2014) - Balaban, Jordan P.; Summers, Adam P.; Wilga, Cheryl A.
ABSTRACT Sharks have cartilaginous elements that support the jaws and are subjected to variable loads. The aim of this study was to understand how these elements, the hyomandibulae, respond to compressive loads, and to describe the structural level mechanical properties of mineralized cartilage. Mechanical stiffness and effective Poisson's ratio of the hyomandibular cartilage were measured in four species of sharks (white‐spotted bamboo, Chiloscyllium plagiosum; spiny dogfish, Squalus acanthias; sandbar, Carcharhinus plumbeus; and dusky smoothhound, Mustelus canis). The former two are suction feeders, while the latter two are bite feeders. The hyomandibulae of suction feeders were expected to be stiffer because of the increased loads on their hyomandibulae. Bamboo sharks, as the strongest suction feeders, have the stiffest hyomandibula with a stiffness of 106.12 MPa. The stiffness of spiny dogfish, sandbar sharks, and dusky smoothhounds were 41.58, 58.00, and 49.62 MPa, respectively. The proportion of the minerals found in the cross‐section of the hyomandibula determines the elements stiffness. Effective Poisson's ratio was measured at low axial strains and was highly variable ranging from 2.3 × 10−5 to 4.3 × 10−1. This implies that the behavior of the hyomandibulae under load will be very different in different species. Furthermore, this wide range of values for the ratio has potential implications for modeling techniques, such as finite element modeling, which use Poisson's ratio as a fundamental input. J. Exp. Zool. 323A: 1–9, 2015. © 2014 Wiley Periodicals, Inc.